Unravelling the clinical heterogeneity of undefined recurrent fever over time in the European registries on Autoinflammation - Vyzhga, Y; Wittkowski, H; Hentgen, V; Georgin-Lavialle, S; Theodoropoulou, A; Fuehner, S; Jesenak, M; Frenkel, J; Papadopoulou-Alataki, E; Anton, Jordi; Olivieri, A Nunzia; Brunner, J; et al. (Pediatric rheumatology online journal, 2024)
BACKGROUND: Systemic autoinflammatory disorders (SAIDs) represent a growing spectrum of diseases characterized by dysregulation of the innate immune system. The most common pediatric autoinflammatory fever syndrome, Periodic Fever, Aphthous Stomatitis, Pharyngitis, Adenitis (PFAPA), has well defined clinical diagnostic criteria, but there is a subset of patients who do not meet these criteria and are classified as undefined autoinflammatory diseases (uAID). This project, endorsed by PRES, supported by the EMERGE fellowship program, aimed to analyze the evolution of symptoms in recurrent fevers without molecular diagnosis in the context of undifferentiated AIDs, focusing on PFAPA and syndrome of undifferentiated recurrent fever (SURF), using data from European AID registries. METHODS: Data of patients with PFAPA, SURF and uSAID were collected from 3 registries including detailed epidemiological, demographic and clinical data, results of the genetic testing and additional laboratory investigations with retrospective application of the modified Marshall and PRINTO/Eurofever classification criteria on the cohort of PFAPA patients and preliminary SURF criteria on uSAID/SURF patients. RESULTS: Clinical presentation of PFAPA is variable and some patients did not fit the conventional PFAPA criteria and exhibit different symptoms. Some patients did not meet the criteria for either PFAPA or SURF, highlighting the heterogeneity within these groups. The study also explored potential overlaps between PFAPA and SURF/uAID, revealing that some patients exhibited symptoms characteristic of both conditions, emphasizing the need for more precise classification criteria. CONCLUSIONS: Patients with recurrent fevers without molecular diagnoses represent a clinically heterogeneous group. Improved classification criteria are needed for both PFAPA and SURF/uAID to accurately identify and manage these patients, ultimately improving clinical outcomes.
Keywords: Stomatitis, Aphthous; Female; Lymphadenitis; Adolescent; mužské pohlaví; Retrospective Studies; lymfadenitida; dědičné zánětlivé autoimunitní nemoci; Recurrence; Infant; kojenec; retrospektivní studie; Humans; Europe; Child, Preschool; faryngitida; Hereditary Autoinflammatory Diseases; Fever; Evropa; registrace; lidé; Pharyngitis; aftózní stomatitida; horečka; ženské pohlaví; Child; recidiva; předškolní dítě; dítě; Registries; Male; mladiství